2018
DOI: 10.2478/sm-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Syrian Students in Turkish Schools: Experiences of Teachers

Abstract: The Syrian civil war affected Turkey so much that approximately three and a half million Syrians live in Turkey. Ministry of Education implemented an inclusive approach to schooling of Syrian asylum-seekers' children by educating them in public schools with their Turkish peers in the same classrooms in 2016 in order to address their educational needs, integration into the Turkish culture, and to prevent generation gap. Education, as a basic human right and as a way of integration into the Turkish society, is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
12
0
4
Order By: Relevance
“…These teachers stated that Syrian students have an insufficient vocabulary and conceptual repertoire, start school without knowing Turkish, and encounter problems due to the difference between the alphabets, and, in general, their inability to speak Turkish. This result matches different research findings (Miller, 2009;Sarıtaş et al, 2016;Biçer and Kılıç, 2017;Keskinkılıç Kara et al, 2017;Erdem, 2017;Bulut et al, 2018;Kiremit et al, 2018;Şahin and Doğan, 2018;Yaşar and Amaç, 2018). For instance, the findings obtained by Bulut et al (2018) revealed that teachers implement the same curriculum for the refugee children whose mother tongue is not Turkish and the children whose mother tongue is Turkish and they do not know how to address such problems since they have not received any training on it.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 90%
See 3 more Smart Citations
“…These teachers stated that Syrian students have an insufficient vocabulary and conceptual repertoire, start school without knowing Turkish, and encounter problems due to the difference between the alphabets, and, in general, their inability to speak Turkish. This result matches different research findings (Miller, 2009;Sarıtaş et al, 2016;Biçer and Kılıç, 2017;Keskinkılıç Kara et al, 2017;Erdem, 2017;Bulut et al, 2018;Kiremit et al, 2018;Şahin and Doğan, 2018;Yaşar and Amaç, 2018). For instance, the findings obtained by Bulut et al (2018) revealed that teachers implement the same curriculum for the refugee children whose mother tongue is not Turkish and the children whose mother tongue is Turkish and they do not know how to address such problems since they have not received any training on it.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 90%
“…Teachers have an important part in the education process and constitute the most affected group searching for solutions. Studies (Aykırı, 2017;Erdem, 2017;Keskinkılıç Kara et al, 2017;Biçer and Kılıç, 2017;Bulut et al, 2018;Kiremit et al, 2018;Şahin and Doğan, 2018;Yaşar and Amaç, 2018) highlight that teachers face various problems during this process. For example, the prominent problems identified in the study carried out by Yaşar and Amaç (2018) are language barrier, lace of family support, and lack of teachers' knowledge and skills concerning refugee students.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Araştırmanın yapıldığı şehir, kendi nüfusu kadar Suriyeli sığınmacı barındıran örnek bir şehirdir. Sığınmacıların çocukları, MEB bünyesindeki okullarda Türk akranlarıyla birlikte eğitim almakta ve Türkçeyi henüz yeterince öğrenemedikleri için bazı zorluklar yaşamaktadırlar (Yaşar ve Amaç, 2017). Bu öğrencilerin birçoğu, öğretmenleri tarafından desteğe ihtiyaç duyan öğrenciler olarak nitelendirilmiş ve proje kapsamında öğretmen adaylarından dil ve diğer akademik konularda destek almışlardır.…”
Section: Tartışma / Sonuç Ve öNerilerunclassified